Analysis of Selected Aspects of a Local Community Safety: A Quantitative and Qualitative Research in A District of Poznan, Poland - Tomasz EWERTOWSKI; Nina KROLL (Communications of International Proceedings, 2024)
The aim of this article is to diagnose the state of safety and the sense of safety in the local community of a selected district of Poznan, and to present proposals for changes and improvements based on the identified issues, which will enhance the level of safety and its perception among the local community. Three selected aspects of community safety were analyzed: the effectiveness of public services, the effectiveness of interactive reporting systems, and the local community's sense of safety. To analyze the selected aspects, original research was conducted. The chosen research tools included a survey based on a personal questionnaire, observation, and in-depth interviews. The results of the research provided insights into specific safety-related issues. Subsequently, the topics related to the selected aspects were assessed. A custom five-point rating scale for community safety effectiveness was developed and used for this purpose. In the final part of the paper, a summary was prepared, and conclusions were drawn. The main findings indicate a relatively low assessment of the safety conditions in the analyzed district and the existence of a gap between the actual state of safety and the perceived safety in the local community. This suggests that residents assess the situation more critically than it actually is – due to a small difference of 3.5/3, we can describe this as a state of mild safety obsession. Based on these conclusions, several changes were proposed to improve safety in the selected aspects.
Keywords: local community; safety; sense of safety; security; safety management.